The Relationship Of Anemia During Pregnancy And The Incident Of Postpartum Bleeding At The Pratama Evi Clinic, Medan Marelan District, Medan City, North Sumatra, 2023 - Maulina Mawaddah; Eka Sylviana Siregar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The prevalence of postpartum anemia is quite large and the effect is significant in many places around the world, this problem has not received adequateattention even in developed countries (Garrido et al., 2017). This type of research uses correlational descriptive with a cross sectional approach. The population in this study were 120 postpartum mothers. The sampling technique is to use the Accidental Sampling Technique. From the results of the study it was known that ofthe 30 postpartum mothers the majority were not anemic as many as 17 people (56.7%) and the minority anemia as many as 13 people (43.3%). Some of them, themajority who experienced Postpartum Bleeding were 16 people (53.3%) and a minority without Postpartum Bleeding were 14 people (46.7%). Based on the Chi Square statistical test, results were obtained where the p value was 0.000 (<0.05), so that Ha was accepted, Ho was rejected, which means that there is a relationshipbetween anemia during pregnancy and the incidence of postpartum hemorrhage at Evi Primary Clinic in 2023. Based on the conclusions, it is hoped that mothers canadd insight especially for mothers giving birth to obey the midwife's recommendations so they can anticipate the incidence of postpartum hemorrhage.